Effectivity of Arbuscular Mycorrhyza Fungi (AMF) and Nitrogen Fertilizer on The Growth and Yield of Sunflower (Helianthus annus L.) - Firsta Ninda Rosadi; Roza Yunita; Jamsari Jamsari (JERAMI : Indonesian Journal of Crop Science, 2021)
One of the main products of sunflower is the seed which is a producer of vegetable oil that is needed in the pharmaceutical industry and the health sector. The price of sunflower seed oil is currently very high for the market but sunflower production in Indonesia is quite low. This potential can be used as the basis for the development of sunflower cultivation in Indonesia. One of the efforts to increase the content of sunflower seed oil is to improve proper cultivation techniques and modifications in cultivation techniques. One of the cultural techniques in increasing production is to get the right dose of nitrogen (N) fertilization. The addition of Arbuscular Mycorrhiza Fungi (AMF) is expected to increase the absorption of N nutrients in the soil, thereby increasing the growth and yield of sunflowers. This study aimed 1) effectivity of AMF and nitrogen fertilizer application with various doses on growth and yield of sunflower, 2) to obtain the right dose of N fertilizer on growth and yield of sunflower The study used a Split-plot Design with 3 replications. The first factor as the main plot is AMF i.e. F0 = without AMF, F1 = with AMF 5 g hole-1. The second factor as a sub-plot is the dose of urea fertilizer with 4 levels i.e. N1 = 50 kg N Ha-1, N2 = 100 kg N Ha-1, N3 = 150 kg N Ha-1, N4 = 200 kg N Ha-1. Observations data were evaluated by analysis of variance if the obtained F count was greater than F table 5% followed by a further test of DNMRT at the 5% significant level. Result showed 1) the effectivity of AMF and nitrogen fertilization on sunflowers was able to increase the number of leaves, accelerate the initiation of flowering, increase the diameter of sunflowers, total seeds per plant, the weight of 100 seeds, and seed production per plant, 2) Economically, the application of nitrogen fertilizer with a dose of 150 kg N Ha-1 is more appropriate in increasing the growth and production of sunflowers